2019
DOI: 10.29007/5jlf
|View full text |Cite
|
Sign up to set email alerts
|

GP-SUM. Gaussian Process Filtering of non-Gaussian Beliefs

Abstract: This work studies the problem of stochastic dynamic filtering and state propagation with complex beliefs. The main contribution is GP-SUM, a filtering algorithm tailored to dynamic systems and observation models expressed as Gaussian Processes (GP), and to states represented as a weighted Sum of Gaussians. The key attribute of GP-SUM is that it does not rely on linearizations of the dynamic or observation models, or on unimodal Gaussian approximations of the belief, hence enables tracking complex state distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Reasoning about the uncertainty in actions and motions is a powerful tool in planning and control [17], [18], [19], [20]. In the context of planar manipulation, Bauza and Rodriguez [20] used Gaussian processes to learn the motion model of planar shapes and to propagate uncertainty using the GP-SUM algorithm. The GP-SUM algorithm is a hybrid Bayes and particle filter; it exploits the Gaussian structure of the motion model to efficiently approximate the distribution over outcomes as a mixture of Gaussians.…”
Section: Uncertainty Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasoning about the uncertainty in actions and motions is a powerful tool in planning and control [17], [18], [19], [20]. In the context of planar manipulation, Bauza and Rodriguez [20] used Gaussian processes to learn the motion model of planar shapes and to propagate uncertainty using the GP-SUM algorithm. The GP-SUM algorithm is a hybrid Bayes and particle filter; it exploits the Gaussian structure of the motion model to efficiently approximate the distribution over outcomes as a mixture of Gaussians.…”
Section: Uncertainty Modelingmentioning
confidence: 99%
“…The GP-SUM algorithm is a hybrid Bayes and particle filter; it exploits the Gaussian structure of the motion model to efficiently approximate the distribution over outcomes as a mixture of Gaussians. Bauza and Rodriguez [20] showed that pushing can exhibit multimodality and their approach is able to capture it. We use the model and algorithm from [20] as benchmarks for our approach and compare the two on the MIT push dataset [5].…”
Section: Uncertainty Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we presented our earlier dataset on planar pushing [1], it has been directly used for: 1) Stochastic modeling: [23,10,17] 2) Modeling from rendered images: [16] 3) Model identification: [24] 4) Learning models for control: [25,26] 5) Filtering: [27] 6) Meta-learning: [28] With this new dataset we hope to further facilitate research in learning models and control.…”
Section: Related Workmentioning
confidence: 99%